Bacteriophages targeting pathogenic bacteria isolated from lumpfish (Cyclopterus lumpus L.) and Atlantic salmon (Salmo salar L.) - Tolås, Anne Helene Paulsen (The University of Bergen, 2021)
Bacterial diseases in aquaculture lead to reduced health and mortality of fish as well as economic consequences for the producer. Antibiotics are an important antimicrobial to control bacterial diseases, however, concerns regarding the potential development and spread of antibiotic resistance genes are rising globally. Other solutions are considered, as the prophylactic or therapeutic use of bacteriophages, natural occurring viruses that infect and kill bacteria. This study aimed to isolate bacteriophages specific to pathogenic bacteria causing problems in Norwegian aquaculture. Among the bacteria causing disease in lumpfish (Cyclopterus lumpus L.) farming are Aeromonas salmonicida, Vibrio anguillarum and Pasteurella sp. Pasteurellosis is also an emerging disease in salmon (Salmo salar L.) farming. A collection of these bacteria were used to screen water samples for bacteriophages by using plaque assays. In addition to previously characterized isolates, bacteria from clinically sick salmon and lumpfish were isolated and sequenced by 16s rRNA sequencing. Water samples were collected from the environment and aquaculture sites. Pasteurella sp. was successfully isolated from clinically sick salmon suffering from pasteurellosis. From lumpfish diagnosed with vibriosis, isolation of V.anguillarum was expected, however, 16s rRNA sequencing showed the presence of Photobacterium spp. and Allivibrio logei. Isolation of bacteriophages was challenging, and target bacteriophages were not found in the majority of water samples. However, when samples from an aquaculture site with salmon diagnosed with pasteurellosis was tested, lysed bacteria were observed in plaque assays, indicating the presence of bacteriophages. Successful isolation of these bacteriophages were not achieved, and this posed a question if prophages present in the genome of Pasteurella sp. could have caused the plaques. Bacteriophages specific for V.anguillarum was not isolated, but a previously isolated bacteriophage showed an effect against pathogenic ...